Network Model of Lower Level Bureaucracy Capacity Building in Community Empowerment Policy Case Study of Street Vendors (PKL) Policy Implementation in South Sulawesi Province - Andriyansah Andriyansah; Rulinawaty Rulinawaty (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
From the results of research on the Lower-Level Bureaucratic Capacity Building Network Model in Community Empowerment Policy: Case Study of Implementation of Limam Foot Vendor (PKL) Policy in South Sulawesi Province. Aims to find out effective implementation strategies so that street vendors can participate in world development, especially specifically in the province of South Sulawesi, precisely in the city of Makassar, the focus in this study includes (a). integrated human resource development in implementing street vendor empowerment policies, (b). partial strengthening of the organization in implementing PKL empowerment policies (c).institutions that are integrated in the collaborative implementation of street vendor empowerment policies. The method of the research results is to use qualitative methods that are case study strategic surveys. The data collection techniques used are in-depth interviews, observation, and documentation. The results of the study show that the development of empowerment coaching.